miR-153-3p Targets βII Spectrin to Regulate Formaldehyde-Induced Cardiomyocyte Apoptosis - Yang, Panyu; Yang, Yanyan; He, Xiangqin; Sun, Pin; Zhang, Ying; Song, Xiaoxia; Tian, Yu; Zong, Tingyu; Ma, Jianmin; Chen, Xiaofei; Lv, Qifeng; Yu, Tao; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Formaldehyde (FA) is ubiquitous in the environment and can be transferred to the fetus through placental circulation, causing miscarriage and congenital heart disease (CHD). Studies have shown that βII spectrin is necessary for cardiomyocyte survival and differentiation, and its loss leads to heart development defects and cardiomyocyte apoptosis. Additionally, previous studies have demonstrated that miRNA is essential in heart development and remodeling. However, whether miRNA regulates FA-induced CHD and cardiomyocyte apoptosis remains unclear. Methods: Using commercially available rat embryonic cardiomyocytes and a rat model of fetal cardiomyocyte apoptosis. Real-time quantitative PCR (RT-qPCR) and Western blot were performed to examine the level of miR-153-3p, βII spectrin, caspase 7, cleaved caspase7, Bax, Bcl-2 expression in embryonic cardiomyocytes and a rat model of fetal cardiomyocyte apoptosis. Apoptotic cell populations were evaluated by flow cytometry and Tunel. Luciferase activity assay and RNA pull-down assay were used to detect the interaction between miR-153-3p and βII spectrin. Masson's trichrome staining detects the degree of tissue fibrosis. Fluorescence in situ hybridization (FISH) and Immunohistochemistry were used to detect the expression of miR-153-3p and βII spectrin in tissues. Results: Using commercially available rat embryonic cardiomyocytes and a rat model of fetal cardiomyocyte apoptosis, our studies indicate that miR-153-3p plays a regulatory role by directly targeting βII spectrin to promote cardiomyocyte apoptosis. miR-153-3p mainly regulates cardiomyocyte apoptosis by regulating the expression of caspase7, further elucidating the importance of apoptosis in heart development. Finally, the results with our animal model revealed that targeting the miR-153-3p/βII spectrin pathway effectively regulated FA-induced damage during heart development. Recovery experiments with miR-153-3p antagomir resulted in the reversal of FA-induced cardiomyocyte apoptosis and fetal cardiac fibrosis. Conclusion: This study investigated the molecular mechanism underpinning the role of βII spectrin in FA-induced CHD and the associated upstream miRNA pathway. The study findings suggest that miR-153-3p may provide a potential target for the clinical diagnosis and treatment of CHD.